Why display motion on packaging? The effect of implied motion on consumer behavior. (January 2022) - Yu, Junwei; Droulers, Olivier; Lacoste-Badie, Sophie
Abstract: Visual packaging elements play a crucial role in influencing consumer behavior in stores. Front of pack (FOP) formats frequently present images of the product in motion (i.e., implied motion), especially in food categories. Despite the popularity of implied motion in real-world business, little research has been done to understand its effect on consumer behavior. To fill this gap, the present study adopts an evolutionary lens to investigate the impact of implied motion as a packaging design technique on consumers' attention, product evaluation, purchase intention and choice. We carried out two experiments using realistic milk and orange juice packaging. Specifically, Experiment 1 was conducted in a lab using an eye tracking method to provide an objective measure of attention. The findings show that implied motion significantly increases visual attention and consequently generates more frequent choices. Using an online experimental design and declarative measures, Experiment 2 indicates that implied motion also enhances freshness, which translates into greater tastiness, product attractiveness and, ultimately, purchase intention. The study provides marketers with an inexpensive yet efficient way to enhance in-store marketing performance by incorporating implied motion into the FOP design.